Ipsilateral lower limb motor performance and its association with gait after stroke. - Pei-Yun Lee; Chih-Hung Chen; Hui-Yu Tseng; Sang-I Lin (PLoS ONE, 2024)
Background and purpose Motor deficits of the ipsilateral lower limb could occur after stroke and may be associated with walking performance. This study aimed to determine whether the accuracy and movement path of targeted movement in the ipsilateral lower limb would be impaired in the chronic stage of stroke and whether this impairment would contribution to gait. Methods Twenty adults with chronic stroke and 20 age-matched controls went through Mini Mental Status Examination (MMSE), and a series of sensorimotor tests. The targeted movement tasks were to place the big toe ipsilateral to the lesion at an external visual target (EXT) or a proprioceptive target (PRO, contralateral big toe) with eyes open (EO) or closed (EC) in a seated position. A motion analysis system was used to obtain the data for the calculation of error distance, deviation from a straight path, and peak toe-height during the targeted movement tasks and gait velocity, step length, step width and step length symmetry of the lower limb ipsilateral to the brain lesion during walking. Results The stroke group had significantly lower MMSE and poorer visual acuity on the ipsilateral side, but did not differ in age or other sensorimotor functions when compared to the controls. For the targeted movement performance, only the deviation in PRO-EC showed significant between-group differences (p = 0.02). Toe-height in both EXT-EO and in PRO-EO was a significant predictor of step length (R2 = 0.294, p = 0.026) and step length symmetry (R2 = 0.359, p = 0.014), respectively. Discussion and conclusions The performance of ipsilateral lower limb targeted movement could be impaired after stroke and was associated with step length and its symmetry. The training of ipsilateral targeted movement with unseen proprioceptive target may be considered in stroke rehabilitation.